Revitalization of the ‘Lamer’ Water Spring in Panggung Village – Malang City (Fakultas Teknik, Universitas Brawijaya, 2023)
Panggung Village is located along Simpang Candi Panggung Road, Mojolangu Subdistrict, Lowokwaru District, Malang City. It is one of the ancient villages in Malang. The majority of its residents are native to the village, having inhabited it for generations. In Panggung Village, there is a historical site called Beji Sari Water Spring, recorded by the Mpu Purwa Prehistoric Objects Conservation Center in Malang. This water spring is one of the three in the Village, with the other two being the Lamer water spring lcoated in the center of the village and the Ngaglik water spring situated at the eastern end of the village. According to the elders and community leaders in Panggung Village, each of these water sources has its own historical significance. One particular water spring, the Lamer water spring, has played a crucial role in the lives of Panggung Village residents. According to the stories passed down by the elders, during the early formation of the village when most residents did not have wells, the relied on the Lamer water spring in the middle of the village for its excellet, clear, and abundant water. Even today, the water quality remains excellent and clear. The Lamer water spring has provided numerous benefits and assistance to the residents, especially in supporting their daily lives. Currently, the Lamer water spring is not well-maintained due to the increasing steepness of the surrounding terrain, making it difficult to access and care for. This poses challenges not only for maintenance but also raises concerns about potential landslides that could damaage the area around the water spring. This community service project aims to revitalize the Lamer water spring, recognizing its historical significance as a physical testament to past events. The historical legacy serves as a learning opportunity for future generations, particularly the youth in Panggung Village who may be unfamiliar or unaware of their village’s history. The goal is to familiarize them with the Lamer water spring and its role in assisting the lives of the residents, setting an example that even a drop of water can be meaningful for life.